Psychedelics and Immunomodulation: Novel Approaches and Therapeutic Opportunities - Szabo, Attila (Frontiers in Immunology, 2015)
Classical psychedelics are psychoactive substances, which, besides their psychopharmacological activity, have also been shown to exert significant modulatory effects on immune responses by altering signaling pathways involved in inflammation, cellular proliferation and cell survival via activating NF-κB and MAPKs. Recently, several neurotransmitter receptors involved in the pharmacology of psychedelics, such as serotonin and sigma-1 receptors, have also been shown to play crucial roles in numerous immunological processes. This emerging field also offers promising treatment modalities in the therapy of various diseases including autoimmune and chronic inflammatory conditions, infections, and cancer. However, the scarcity of available review literature renders the topic unclear and obscure, mostly posing psychedelics as illicit drugs of abuse and not as physiologically relevant molecules or as possible agents of future pharmacotherapies. In this paper, the immunomodulatory potential of classical serotonergic psychedelics, including N,N-dimethyltryptamine (DMT), 5-methoxy-N,N-dimethyltryptamine (5-MeO-DMT), lysergic acid diethylamide (LSD), 2,5-dimethoxy-4-iodoamphetamine (DOI) and 3,4-methylenedioxy-methamphetamine (MDMA) will be discussed from a perspective of molecular immunology and pharmacology. Special attention will be given to the functional interaction of serotonin and sigma-1 receptors and their cross-talk with Toll-like and RIG-I-like pattern recognition receptor-mediated signaling. Furthermore, novel approaches will be suggested feasible for the treatment of diseases with chronic inflammatory etiology and pathology, such as atherosclerosis, rheumatoid arthritis, multiple sclerosis, schizophrenia, depression and Alzheimer's disease.